The effectiveness of the epworth sleepiness scale as an auxiliary resource in the diagnosis of obstructive sleep apnea syndrome - doi:10.5020/18061230.2013.p56 - Ingrid Correia Nogueira; Priscilla Oliveira Azevedo; Clarissa Bentes de Araujo Magalhaes; Vera Maria Andrade Lacerda; Ana Cristhina de Oliveira Brasil; Daniela Gardano Bucharles Mont´Alverne (Universidade de Fortaleza, 2013)
Objective: To analyze the effectiveness of the Epworth Sleepiness Scale (ESS) as an auxiliary resource in the diagnosis of the Obstructive Sleep Apnea Syndrome (OSAS). Methods: Observational study, with a retrospective phase and a prospective one, comprising 475 patients who sought the Sleep Study Center in Fortaleza (Centro de Estudo do Sono de Fortaleza - CESF). Data was collected from medical records, which comprises ESS, amidst some questionnaires prepared by CESF professionals and answered by the patients. The study compared the results raised by the ESS to the polysomnography data. Data analysis was performed on SPSS, using Pearson chi-square test, considering as statistically significant p-value < 0.05. Results: The male, the group aged 50 to 60, and those with body mass index> 30 kg/m2 were the most affected by OSAS, with 38.9%, 41% and 45.1%, respectively. A significant relationship was found between ESS score and OSAS (p = 0,001), showing that 25.9% (n = 123) of patients, who had values higher than 10 in the ESS, were diagnosed with OSAS. Conclusions: Data on this study shows that ESS fits as an auxiliary resource in the diagnosis of OSAS and it may be applied by any health professional while taking the clinical history. However, clinical signs are not sufficient to diagnose it, so that polysomnography is still required.